Modelagem da sobrevivência de Salmonella enterica em flocos de coco desidratados convencionalmente e osmoticamente - Silva, Ruthchelly Tavares da (2021)
Salmonella enterica is one of the main etiologic agents of diarrheal diseases worldwide. In Brazil, this pathogen is among the main pathogens involved in foodborne disease outbreaks. The involvement of dehydrated foods in these outbreaks has increased, with emphasis on dehydrated coconut. Therefore, the present study evaluated the behavior of S. enterica (S. Enteritidis PT4, S. Typhimurium PT4, S. Bredeney, S. Muenster and S. Agona) in dehydrated coconut-flakes in a conventional and osmotic-dehydration during storage. The survival of S. enterica were evaluated through the enumeration of viable cells in four possible storage scenarios at room temperature (25 ± 1 ºC) and/or refrigerated temperature (7 ± 1 ºC) every 7 days for 120 storage days. Damage to membrane integrity, the membrane potential and the metabolic activity of S. enterica cells were evaluated 1 day after conventional or osmotic dehydration and after 120 days of storage at 7 or 25 ºC using flow cytometry. Water activity (aw) between 0.35 ± 0.03 and 0.34 ± 0.02 were observed for conventionally dehydrated coconut-flakes, while osmotically dehydrated coconut-flakes showed average aw values in the range of 0.31 ± 0.03 and 0.29 ± 0.03 among the evaluated scenarios during the observation period. Conventional-dehydration and osmotic-dehydration reduced less than 1 log CFU.g-1 of S. enterica in coconut-flakes. Log-linear + tail and log-linear + shoulder + tail models showed good fit the survival curves of S. enterica in conventionally and osmotically dehydrated coconut-flakes over storage, respectively with R2 > 0.9 in most scenarios. Lower S. enterica inactivation rates (kmax 0.02 to 0.04/days) were observed in coconut-flakes conventionally dehydrated compared to osmotically dehydrated (kmax 0.16 to 0.20/days). Changes in storage temperature did not affect the behavior of S. enterica in dehydrated coconut-flakes conventionally or osmotically dehydrated coconut-flakes. Larger subpopulations of S. enterica cells with damaged membrane and without metabolic activity were observed in conventionally dehydrated coconut-flakes in the beginning of storage, however it decreased after 120 days of storage. In contrast, the damaged S. enterica subpopulations in osmotically dehydrated coconut-flakes increased or did not change at the end of storage. Results show the S. enterica behavior in dehydrated coconut-flakes over four-month storage and alert for the great survival when conventional dehydration is used, and possible occurrence of cell repair.